(Re)Moving Indigenous Knowledge Boundaries: A Review of Library and Archival Collection Literature since the Enactment of the Native American Graves Protection and Repatriation Act (NAGPRA). Issue 1 (2nd January 2023) - Reijerkerk, Dana; Nyitray, Kristen J.
Abstract: The enactment of the Native American Graves Protection and Repatriation Act (NAGPRA) in 1990 marked a turning point for the stewardship and preservation of Indigenous cultural heritage materials. In the past 30 years, themes in library and archival collection literature have also shifted to emphasize decolonization, equity, diversity, and inclusion. This article provides an overview of scholarship on Indigenous and Indigenous-related research materials with evidence of advocacy and integration of decolonization methodologies in acquisitions, bibliographic sources and tools, digitization, access, and associated curriculum. Discussion of issues yet to be remediated and areas for further research are also presented.